Advanced EM shielding through novel CNT fence wall transfer technology - Lum, Lucas Yu Xiang (Nanyang Technological University, 2024)
With the miniaturisation of modern electronic circuits, new circuit and packaging designs must be smaller and lighter whilst encompassing greater functionalities. The high operating frequency within the reduced printed circuit board (PCB) real estate of these new circuits results in problems related to signal integrity. These problems place an enormous pressure on current board level EM shielding and isolation methods. As such, to maintain the signal integrity and the electromagnetic (EM) compliance in PCB circuits, modern shielding and isolation methods face a compromise between their effectiveness and the amount of real estate they can occupy. One method to tackle the compromise is through the supplementation of current EM compliance techniques with a lightweight nanomaterial such as carbon nanotubes (CNTs). CNTs have been widely used by the industry in the macro scale with proven performance. However, the widespread micro-scale integration of CNTs has been met by the inability to integrate at low temperatures and in tight, narrow, and complex spaces of modern PCBs. Thus, this report aims to develop and implement an industrially viable, turnkey transfer-application of CNTs as a board-level electromagnetic shielding and isolation supplementation method. This work reports an investigation into the anisotropic microwave electronic properties of vertically aligned CNTs (VACNTs). Free-standing VACNT arrays were found to be partially anisotropic, displaying varying degrees of lossy dielectric, and diamagnetic behaviour. A semi-automated method of transferring VACNTs onto circuit boards was developed, vastly improving the yield and repeatability of transfer over current methods to allow for the turnkey v integration of CNT based board-level EM shielding. VACNT arrays are transferred onto circuit boards through an optimised process, forming a stable, electrically conductive bond with a measured low resistivity of 106.25 mΩ ·cm. With a classical via fence setup, it was shown that an 18 dB improvement in EM isolation can be obtained together with a decrease in via fence width. Following this, the improved technique can be used as an application for VACNT based board-level EM isolation and shielding, implementing isolation traces onto space-constrained electronic devices to improve their EMC performance.